Development of Sets-Based Booklets to Improve Critical Thinking Skills and the Effectiveness of Biotechnology Learning in SMA/MA - Nugraini, Anisa Ratna; Iswari, Retno Sri; Anggraito, Yustinus Ulung (Journal of Innovative Science Education, 2022)
Characteristics of learning biotechnology is the existence of a process and product related to everyday life. Therefore, an effective learning process is needed and supported by relevant learning resources. This study aims to analyze the validity of SETS-based biotechnology material booklets used in biotechnology learning. Describe the characteristics of SETS-based biotechnology material booklets. Analyzing students' critical thinking skills in biotechnology learning using SETS-based booklets. Analyzing the effectiveness of biotechnology learning using a SETS-based booklet This research is a research and development (R&D) study. The booklet development trial was conducted in 4 schools, with the research subjects being class XII students in each school. Applicative and meaningful learning of biotechnology can be achieved, one of which is by learning using the SETS vision booklet. The SETS vision booklet contains more concise material, accompanied by attractive, colorful pictures that can effectively improve student learning outcomes. The N-gain value obtained is 0.3-0.4 with the medium category and classical completeness reaching 60%. Critical thinking skills that are formed through active learning using SETS vision booklets are 71% -80% in the high category. Critical thinking skills in integrating SETS elements in biotechnology learning can make it easier for students to understand knowledge concepts, so that they can increase learning effectiveness, namely improving learning outcomes and classical mastery.